"Maybe useful to the future generation but not my own": How "useful" is Mandarin really for contemporary Hoisan-heritage Chinese Americans in the San Francisco Bay Area?. (January 2021) - Leung, Genevieve
Abstract: This paper examines non-Mandarin-speaking Chinese Americans in the San Francisco Bay Area who speak a variety of Cantonese called Hoisan-wa, whose histories and experiences are often muted in wider contemporary academic and public "Mandarin-as-Chinese" discourses. Drawing on 93 interviews, I focus on language awareness of Chinese(s) through: a) participants' anchorings of Chinese varieties; b) self-reported fluency data; c) the use of the term "Chinese. The data suggests that if we aim to promote equitable "Chinese" language maintenance opportunities for all Chinese Americans, rather than viewing Chinese language acquisition as linear and limited to only one variety at a time, there needs to be more inclusion of the diverse Chinese languages that are in the local communities, Hoisan-wa among them. Highlights: Chinese Americans in the San Francisco Bay Area don't find Mandarin centrally relevant to their lives. "Chinese" does not refer to Mandarin for their everyday discussions about language. More attention needs to be paid to these distinctions across Chinese varieties.